ANALISIS LAPORAN KEUANGAN BERDASARKAN RASIO LIKUIDITAS DAN SOLVABILITAS PADA PT BANK RAKYAT INDONESIA, Tbk Periode 2017-2021 - Alessandro Timothy Nathanael (2022)
A bank is a business entity that collects funds from the public in the form of deposits and distributes them to the public in the form of credit or other forms to improve the standard of living of the community, and the bank has the main task of collecting and distributing funds from and to the community, where the bank as a trust institution must have adequate liquidity. There are two analytical methods used by each financial statement analyzer, namely horizontal analysis (dynamic analysis) which is an analysis by comparing financial statements for several periods, so that their development will be known and vertical analysis (static analysis), namely if the analyzed financial statements only cover one period, namely by comparing one post with another in the financial statements. From the analysis above, the cash ratio of PT Bank Rakyat Indonesia Tbk decreased in 2018 and in 2020 due to an increase in current liabilities, the cause of the increase in current liabilities of customer deposits in current accounts, savings, and time deposits. In 2019 and 2021, the company's cash ratio increased, due to an increase in current liabilities, causing an increase in current liabilities of customer deposits in current accounts, savings, and time deposits. However, cash in 2021 decreased due to foreign currency equivalent income decreasing compared to 2020. Financial statement analysis is one way to find out the development of performance. There are five stages in analyzing financial statements, reviewing financial statement data, making calculations, comparing the results of calculations that have been obtained, interpreting various problems found, and looking for and providing solutions to various problems found.